2014
DOI: 10.5370/jeet.2014.9.2.649
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Quantum Model for Cylindrical Surrounding Gate MOSFETs using High-k Dielectrics

Abstract: -In this paper, an analytical model for Surrounding Gate (SG) metal-oxide-semiconductor field effect transistors (MOSFETs) considering quantum effects is presented. To achieve this goal, we have used variational approach for solving the Poission and Schrodinger equations. This model is developed to provide an analytical expression for inversion charge distribution function for all regions of device operation. This expression is used to calculate the other important parameters like inversion charge density, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…It is also concluded that Moore's law is inappropriate since it was practically found that we cannot further reduce the channel length [4]. Efforts are being made to reduce the shortchannel effects which have led to the discovery of other nanodevices such as MUGFET [5][6][7], FinFET [8], tunnel FET [9], nanowire TFET [10], and so on. The need for high accuracy in bonding and reactions at the atomic level fits graphene for this role [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is also concluded that Moore's law is inappropriate since it was practically found that we cannot further reduce the channel length [4]. Efforts are being made to reduce the shortchannel effects which have led to the discovery of other nanodevices such as MUGFET [5][6][7], FinFET [8], tunnel FET [9], nanowire TFET [10], and so on. The need for high accuracy in bonding and reactions at the atomic level fits graphene for this role [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the asymmetric behavior of the heterostructure under lap double gate MOSFET was analyzed extensively. Until now, researchers have been mainly investigating different aspects of InGaAs-channel MOSFETs for digital applications and for analog/mixed-signal applications [10][11][12]. The impact of different barrier layers on the analog performance and digital performance of an InGaAs MOSFET was also investigated.…”
Section: Introductionmentioning
confidence: 99%